Plasma activated PVDF-BaTiO3 composite nanofiber scaffolds loaded with vancomycin for enhancing biocompatibility and piezoelectric response - Vida Fathollahzadeh; Mehdi Khodaei; Sara Emadi; Kamal Hajisharifi (Scientific Reports)
Abstract Scaffolds engineered with piezoelectric properties offer a promising strategy for enhancing bone regeneration by converting mechanical stimuli into electrical cues that promote osteogenic activity. In this study, drug-loaded piezoelectric nanofiber scaffolds composed of polyvinylidene fluoride (PVDF) and varying concentrations of nano-sized barium titanate (BaTiO3; BTO) were fabricated and evaluated for their mechanical, piezoelectric, antibacterial, and biological performance. Nanofiber scaffolds containing β-phase polyvinylidene fluoride were produced via electrospinning, where the incorporation of barium titanate nanoceramics as nucleating agents, combined with simultaneous stretching and high-voltage application, promoted β-phase formation. This process enhanced the piezoelectric behavior of polyvinylidene fluoride, with the highest output voltage (1.56 mV) observed in scaffolds containing 15 wt% barium titanates. Cold plasma treatment was employed to improve nanofiber hydrophilicity, enhancing scaffold wettability and bioactivity. Vancomycin-loaded scaffolds demonstrated sustained drug release, effective antibacterial activity against Staphylococcus aureus (S. aureus), and controlled biodegradability. Mechanical testing revealed that barium titanate addition up to 10 wt% improved tensile strength and stress transfer capacity, while higher loading (> 10 wt%) resulted in nanoparticle aggregation and reduced mechanical performance. In vitro assays confirmed scaffold biocompatibility, supporting cell adhesion, proliferation, and osteogenic differentiation. These multifunctional polyvinylidene fluoride nanocomposites with barium titanate particles offer a promising platform for bone tissue engineering by integrating mechanical stimulation, drug delivery, and cellular support.